Labor income trends in Kazakhstan - Kurmangaliyeva, L.; Aimagambetov, E.; Jazykbayeva, B.; Кареlуик, Z. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: To research the labor income of the population in the Republic of Kazakhstanin the context of the growth and development of the country's economy.The Subject of the Study is the employment trends in the labor market of Kazakhstan, along with the regulations that have been developed to manifest economic transformation. Methods: The researcher conducted immersive empirical research from peer-reviewed sources, using comparative and component analysis. Findings: The labor trend of Kazakhstan can be categorized into four stages that illustrate each major transformation in the labor market. Conclusions: The current state of Kazakhstan's labor market has been influenced by many factors, including structural changes, market conditions, economic dynamics, information technology and the COVID-19 epidemic. The authors identified four main trends throughout the article in terms of labor income. At the first stage of the development of the Kazakh labor market, there were no relevant legislative guidelines; the second stage included the creation of a legal framework. The third and fourth stages are focused on improving the current labor legislation.
Қазақстандағы еңбек табыстарының тенденциялары
Тенденции трудовых доходов в Казахстане
Keywords: employment; Labor; shadow economy; Gross Domestic Product (GDP); Kazakhstan’s labor market; Information Technology (IT).